2021
DOI: 10.1101/2021.12.28.474380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis of SARS-CoV-2 Omicron immune evasion and receptor engagement

Abstract: The SARS-CoV-2 Omicron variant of concern evades antibody mediated immunity with an unprecedented magnitude due to accumulation of numerous spike mutations. To understand the Omicron antigenic shift, we determined cryo-electron microscopy and X-ray crystal structures of the spike and RBD bound to the broadly neutralizing sarbecovirus monoclonal antibody (mAb) S309 (the parent mAb of sotrovimab) and to the human ACE2 receptor. We provide a structural framework for understanding the marked reduction of binding o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 74 publications
2
18
0
Order By: Relevance
“…Accordingly S/Q493R (as occurs in BA.1), escapes some class 2 neutralizing antibodies 26 , S/Q493R and S/Q493K escape mutations have been selected in VSV in vitro experiments 28 , and the S/Q493K mutation has arisen previously in the context of a chronic SARS-CoV-2 infection 29 . The S/Q498R and S/Q493R mutations also yield two additional salt bridges when binding human ACE2 10,30 and it is likely that the increased affinity of BA.1 Spike for human ACE2 relative to that of Alpha, Beta, Delta and Wuhan-Hu-1 79 will further decrease its sensitivity to neutralisation. Cluster region 3 in the fusion domain (yellow sites in Figure 5): codons/amino acids S/764, S/856, S/954, S/969, S/981; a region of Spike currently not known to be targeted by neutralizing antibodies. The S/N764K, S/N856K and S/N969K mutations are likely to enhance interactions between the S1 and S2 subunits of the BA.1 Spike and are likely to contribute to reduced S1 shedding following proteolytic cleavage of the polybasic S1/S2 site 10,31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly S/Q493R (as occurs in BA.1), escapes some class 2 neutralizing antibodies 26 , S/Q493R and S/Q493K escape mutations have been selected in VSV in vitro experiments 28 , and the S/Q493K mutation has arisen previously in the context of a chronic SARS-CoV-2 infection 29 . The S/Q498R and S/Q493R mutations also yield two additional salt bridges when binding human ACE2 10,30 and it is likely that the increased affinity of BA.1 Spike for human ACE2 relative to that of Alpha, Beta, Delta and Wuhan-Hu-1 79 will further decrease its sensitivity to neutralisation. Cluster region 3 in the fusion domain (yellow sites in Figure 5): codons/amino acids S/764, S/856, S/954, S/969, S/981; a region of Spike currently not known to be targeted by neutralizing antibodies. The S/N764K, S/N856K and S/N969K mutations are likely to enhance interactions between the S1 and S2 subunits of the BA.1 Spike and are likely to contribute to reduced S1 shedding following proteolytic cleavage of the polybasic S1/S2 site 10,31 …”
Section: Resultsmentioning
confidence: 99%
“…Cluster region 3 in the fusion domain (yellow sites in Figure 5): codons/amino acids S/764, S/856, S/954, S/969, S/981; a region of Spike currently not known to be targeted by neutralizing antibodies. The S/N764K, S/N856K and S/N969K mutations are likely to enhance interactions between the S1 and S2 subunits of the BA.1 Spike and are likely to contribute to reduced S1 shedding following proteolytic cleavage of the polybasic S1/S2 site 10,31…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the Omicron RBD has a 2-2.5-fold enhanced binding affinity for ACE2 relative to the Wuhan-Hu-1 RBD (Table 1, Supplementary Figure 5), in line with recent surface plasmon resonance findings 8,9 .As previously observed for the Alpha RBD, which only harbors the N501Y mutation 10 , the modulation of binding is mediated by changes in ACE2 binding off rates. Although the K417N mutation is known to dampen ACE2 engagement 10,11 , a recently determined crystal structure of ACE2-bound Omicron RBD revealed that Q493R and Q498R introduce additional electrostatic interactions with ACE2 residues E35 and D38, respectively 11 , whereas S477N enables hydrogen-bonding with ACE2 S19. Collectively, these mutations strengthen ACE2 binding, relative to the ancestral isolate.…”
Section: Omicron Spike Binds Ace2 With Enhanced Affinitymentioning
confidence: 99%
“…Although the K417N mutation is known to dampen ACE2 engagement 10,11 , a recently determined crystal structure of ACE2-bound Omicron RBD revealed that Q493R and Q498R introduce additional electrostatic interactions with ACE2 residues E35 and D38, respectively 11 , whereas S477N enables hydrogen-bonding with ACE2 S19. Collectively, these mutations strengthen ACE2 binding, relative to the ancestral isolate.…”
Section: Omicron Spike Binds Ace2 With Enhanced a Nitymentioning
confidence: 99%